Antioxidant compounds and activity from the leaf of the mistletoe (Dendrophthoe pentandra (L.) Miq.) on Duku plant (Lansium domesticum Corr.) - Salni Salni; Hanifa Marisa; Putri Mayasari (Universitas Ahmad Dahlan, 2023)
Mistletoes or benalu in Indonesia is a parasitic plant that can live on a variety of hosts. In this study determined the antioxidant activity of mistletoes living on Duku (Lansium domesticum Corr.) was Dendrophthoe pentandra (L.) Miq. The aim of the study determine antioxidant activity used n-hexane, ethyl acetate, and methanol water fractions, and determine the compound groups and the IC50 values. The research methods used were extraction by maceration, fractionation by liquid fractionation method, isolation by vacuum liquid chromatography (VLC) and column chromatography, and antioxidant activity test with DPPH. The results showed that the n-hexane and ethyl acetate fractions which had antioxidant activity and the methanol fraction were inactive. From the n-hexane fraction, the isolates NH.1 and NH.3 were obtained, the former of which belongs to terpenoids, while the latter belongs to flavonoids. From the ethyl acetate fraction, the isolate EA.3, which also belongs to flavonoids, was obtained. The isolate NH.1 has an IC50 value of 151.35 g/mL with weak antioxidant activity, while the isolate NH.3 has 96.64 g/mL, and EA.3 has 78.37 g/mL with moderate antioxidant activity.